Interpersonal Meaning Analysis in Short Story of Hans Chriatian Andersen The Real Princess - Setyowati, Lusi Ayu, Dra. Malikatul Laila, M. Hum, Dra. Siti Zuhriah Ariatmi, M. Hum (2016)
The research paper analyzes the interpersonal meaning realized in the short story of Hans Christian Andersen The Real Princess. The study aims (1) to identify the interpersonal meaning realized in the short story and (2) to reveal the speech function of language use in the short story. The type of this research is descriptive qualitative research. The object of the research is the interpersonal meaning analysis of clauses as exchange in the short story of Hans Christian Andersen The Real Princess. The data of this study is the clauses as exchange in the short story of Hans Christian Andersen The Real Princess. Data source used in this research are the documentation of the data research paper. The researcher uses observation and documentation in collecting data. The data are analyzed by using description method. The text entitled The Real Princess by Hans Christian Andersen is categorized into the text which uses declarative mood type the most (98%) which indicates the position of the author as a provider of information and the readers as the recipient of information. The clauses in the text are said by temporal deicticity or finite tense the most (93%), while the modality deicticity only appears a little (7%) which indicates that the author has no right to persuade the readers because the genre of the text is narrative which functions only to entertain the readers. The personal pronoun which is mostly used in the text is the third personal pronoun (83%) and the first personal pronoun appears only a little (17%) which indicates that the participants in the text is not the author himself but the other people. There are only two speech function found in the short story of Hans Christian Andersen The Real Princess, statement and question. Statement is mostly appeared in the text which reaches precentage 98% whereas question only reaches precentage 2%. So it can be concluded that the speech function used in the text is statement which functions to give information. Keyword: interpersonal meaning, mood, modality, pronoun, speech function